2012
DOI: 10.7750/biodiscovery.2012.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oral lesions in HIV infected adult population of Mangalore, Karnataka, India

Abstract: The aim of this study was to find the prevalence of oral lesions in human immunodeficiency virus (HIV) positive patients and investigate if there was a relationship between oral manifestations and the level of immunosuppression. 125 patients infected with HIV in the age group of 20-40 years were examined for the presence of different oral lesions according to the EEC criterion. The CD4 count, as well as any therapy being instituted was recorded and correlated with the oral manifestations seen.Comparison of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 14 publications
0
10
0
2
Order By: Relevance
“…Oral lesions were found in 63% (n=22) of the patients in this study but Ceballos-Salobreña et al [17] had reported a lower frequency of oral lesions (up to 53%) than the present study in patients on ART. Higher frequency of oral lesions in the present study may be due to the fact that most patients in this study (n=22) had CD4+lymphocyte count <350 cells/mm3 which is considered as the state of advanced immunosuppression according to WHO immunological classification system [10]. On clinical examination, chronic periodontitis was seen in 20% (n=7) cases with one patient (2.9%) having linear gingival erythema (minor form of necrotizing periodontitis).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Oral lesions were found in 63% (n=22) of the patients in this study but Ceballos-Salobreña et al [17] had reported a lower frequency of oral lesions (up to 53%) than the present study in patients on ART. Higher frequency of oral lesions in the present study may be due to the fact that most patients in this study (n=22) had CD4+lymphocyte count <350 cells/mm3 which is considered as the state of advanced immunosuppression according to WHO immunological classification system [10]. On clinical examination, chronic periodontitis was seen in 20% (n=7) cases with one patient (2.9%) having linear gingival erythema (minor form of necrotizing periodontitis).…”
Section: Discussionmentioning
confidence: 55%
“…CD4+ lymphocyte count was quantitatively grouped as <350 cells/mm 3 (Group 1) and >350 cells/mm 3 (Group 2). This cut point of 350 cells/mm 3 was used for grouping because according to WHO immunological classification, it is the state of advanced immunosuppression [10]. Group 1 comprised of n=22 (63%) while Group 2 had n=13 (37.1%) patients.…”
Section: Resultsmentioning
confidence: 99%
“…22 The total antioxidant level also decreased with decrease in CD4 count which could be used as biomarkers for correlation with disease progression in HIV infected individuals. 23 Similarly the nitric oxide (NO 2 þ NO 3 ) concentration in saliva could serve as an indicator of HIV replication and progression of disease as seen in the present study.…”
Section: Discussionmentioning
confidence: 92%
“…20,21 Also our study on prevalence of oral lesions in human immunodeficiency virus (HIV) positive patients showed association between number of oral lesions and CD4þ count in HIV positive patients. 1 There is a soaring need for convenient and simple point-of-care diagnostic tools in developing countries, where many health risks and illnesses remain poorly defined. Information concerning the burden of disease, guidelines for health maintenance, and disease management are seriously inadequate, resulting in severe spread of disease and high death rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation